An Asymptomatic, Supratentorial, Remote Epidural Hematoma Following Posterior Fossa Surgery - Ozturk, Yasar; Ozturk, Sait; Yaman, Mesut Emre; Ayberk, Giyas (Aves, 2017)
An epidural hematoma (EDH) following posterior fossa surgery is extremely rarely reported. We report the case of a 49-yearold woman diagnosed with cerebellar lesions and hydrocephalus. The patient underwent left paramedian suboccipital craniotomy, and total resection of the lesion was performed. After the surgery, the patient was transferred to the intensive care unit with a Glasgow coma score of 15. Because the patient was neurologically stable, computed tomography (CT) was performed on the first postoperative day. A right, frontal, large EDH was seen on the CT image without any complaint and neurological deterioration. EDH evacuation was performed by right frontal craniotomy, and the patient was discharged with full recovery. This case reinforces the importance of a close follow-up and the early imaging of posterior fossa tumors, particularly with hydrocephalus, for not overlooking this rare, but serious, complication, even if a patient is clinically silent.
Keywords: Epidural; posterior fossa; supratentorial; remote; hematoma